ANALYSIS OF FACTORS THAT INFLUENCE PRODUCTION OF RICE FARMING VARIETY OF SIAM EPANG AT SUB DISTRICT OF SERUYAN HILIR - Lili Winarti; Rokman Permadi; Imam Mahfud (Universitas Muhammadiyah Jember, 2019)
Increasing paddy production at Sub-District of Seruyan Hilir is expected to be able to increase income for farmers for increasing the welfare of each farmer family. The purpose of this study was to determine the effect of the area of land, seed, labor in the family, labor outside the family, fertilizer, and pesticides on the production of paddy of Siam Epang Varieties at Sub District of Seruyan Hiir. Study field was at Subdistrict of Seruyan Hilir, Seruyan Regency. Data in this research are primary and secondary data, sample are 86 farmers is choosen by stratified random sampling technique, data collecting method using interview method, questionnaire and literature study and data processing done using Eviews 7 software, the method used is the least squares method (Ordinary Least Squares) in a regression model that produces the best linear unbias estimator (Best Linear Unbias Estimator). The result of data analysis showsthat the factors that have positive and significant influence on the production level of paddy Siam Epang Varieties in Subdistrict of Seruyan Hilir are land area, fertilizer and pesticide with coefficient value are 1.009, 0.355, and 0,248. While the factors that have negative and insignificant effect on the level of production are seeds, TKDK , and TKLK, with coefficient values are -0.131, -0.210, and -0.080. The R2 value is 0.847 means that 84.7 percent of paddy production can be explained by all factors in this study.